2020
DOI: 10.1016/j.fuel.2019.116719
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of copper leaching on combustion characteristics and particulate emissions in HPCR diesel engines

Abstract: A helicoidally shaped copper duct was installed along the fuel line just before the high pressure pump. The impact of fuel contamination from this copper duct on combustion and emission characteristics of a Direct Injection High Pressure Common Rail (DI HPCR) diesel engine was investigated. The copper duct constitutes the core of a fuel conditioning device, powered from the battery. A single cylinder Ricardo Hydra research engine with the cylinder head, piston assembly and crankshaft from a production 2.2 L DI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…If this is happening and how the emissions are affected is not clear, but at our testing the results were not promising. A system that applied voltage at a copper coil, [11], similar to the fuel magnetic device of our study, concluded that it was possible to notice a particulate reduction. The explanation was that the copper leached in the fuel catalytically aided the combustion, but the effect was noticeable only when the fuel was in the tank for some time.…”
Section: Discussionmentioning
confidence: 65%
“…If this is happening and how the emissions are affected is not clear, but at our testing the results were not promising. A system that applied voltage at a copper coil, [11], similar to the fuel magnetic device of our study, concluded that it was possible to notice a particulate reduction. The explanation was that the copper leached in the fuel catalytically aided the combustion, but the effect was noticeable only when the fuel was in the tank for some time.…”
Section: Discussionmentioning
confidence: 65%
“…As mentioned above, the increase in injection pressure is considered as a promising approach to enhance combustion behaviors [9][10][11][12][13]. High-pressure injected diesel fuel could improve the engine performance and reduce particulate matter [14][15][16][17][18]. In addition to that, the increased injection pressure tends to accelerate the vaporization of droplets and the preparation of the combustible mixture [19][20][21][22][23].…”
Section: Diesel Combustion Processmentioning
confidence: 99%
“…This is purposely to develop efficient ways for energy generation and conservation that avoid the production of greenhouse gases that contribute to climate change [13,14]. Improving performance indices such as thermal efficiency of thermal power plant plays a fundamental role in reducing consumption of limited energy resources and environmental impacts [15,16]. Performance improvements in thermodynamic cycles for efficient production of a steam thermal power plant have become increasingly important in the actual worldwide sustainability context due to its implications of net incremental power output and investment cost savings [17,18].…”
Section: Introductionmentioning
confidence: 99%